Outcomes of in vitro fertilization pregnancies complicated by subchorionic hematoma detected on first-trimester ultrasound - Kelsey L. Anderson, M.D; Patricia T. Jimenez, M.D; Kenan R. Omurtag, M.D; Emily S. Jungheim, M.D., M.S.C.I (Elsevier, 2020)
Objective: To estimate the association between subchorionic hematoma (SCH) on ultrasound and pregnancy outcomes in in vitro fertilization (IVF) pregnancies. Design: Institutional Review Board-approved, retrospective cohort study. Setting: Tertiary care university-based facility. Patient(s): In this study, 1,004 patients who underwent IVF with a viable singleton pregnancy from January 1, 2009 through December 31, 2017. Intervention(s): Subchorionic hematoma versus no hematoma diagnosed on first-trimester ultrasound. Main Outcome Measure(s): Live birth, preterm birth, and spontaneous abortion. Result(s): We found that 1,004 women met the criteria and 187 (18.6%) had an SCH. In bivariate and multivariate regression models, there were no associations between SCH and the outcomes of live birth, preterm birth, or birth weight. Conclusion(s): Subchorionic hematoma detected on first-trimester ultrasound after IVF is not associated with probability of live birth, probability of preterm birth, or infant birth weight in this patient population.